O-ring-modularized triboelectric nanogenerator for robust blue energy harvesting in all-sea areas. (1st December 2022) - Li, Haohua; Liang, Chuangjian; Ning, Heng; Liu, Jiaqi; Zheng, Changyue; Li, Jiayu; Yao, Huilu; Peng, Yan; Wan, Lingyu; Liu, Guanlin
Abstract: Triboelectric nanogenerator (TENG) has recently emerged as one of the most promising technologies for capturing low-frequency ocean energy. However, TENG has some disadvantages, such as low volumetric energy density, poor versatility, and poor anti-storm ability, limiting its commercialization. In this study, an O-ring-like TENG (O-TENG) for blue energy harvesting is introduced. This generator can be prepared by flexible splicing of fan-ring-shaped TENG blocks with different angles. The modular design of the O-TENG not only realizes omnidirectional wave energy harvesting but also regulates its response frequency spectrum based on the surroundings, thereby enhancing the energy capture efficiency of the TENG array. The effect of the configuration parameters of the oscillation frequency and swing amplitude was systematically investigated to optimize the output performance of the O-TENG, and a maximum transfer charge of 29.90 μC was obtained. Furthermore, the O-TENG exhibited almost the same charging efficiency even when placed upside-down, demonstrating its anti-storm ability against strong winds and wave interferences. Experimentally, O-TENG can efficiently capture wave energy on the wave pool and drive commercial RF modules to realize wireless signal transmission successfully. This work demonstrates that O-TENGs can capture wave energy and are a potential energy source for ocean monitoring systems, promoting the construction of the IoTs. Graphical Abstract: This paper introduces a multi-angle, spliceable, and top-down symmetric O-ring-like TENG (O-TENG) for robust harvesting of ocean wave energy. The modular design of the O-TENG not only realizes omnidirectional wave energy harvesting but also regulates its response frequency spectrum based on the surroundings, thereby enhancing the energy capture efficiency of the TENG array. ga1 Highlights: The O-ring structure and modular design provide wide, adjustable frequency response, and easy replacement of failed modules. The O-TENG could maintain the original and high output after overturning under an extreme offshore environment. The RF-based wireless signal transmission and other electronics are realized by an O-TENG.